Public Relations Discourse on X (Twitter) and Analysis of Public Relations - Özer Alper, Deniz (LSPR Institute of Communication & Business, 2024)
In the twenty-first century, public relations gained a new form along with digital media, as well as having a wider area of dialogue. Especially social media offers new opportunities for the development of public relations strategies that focus on building and developing relationships with sharers. While creating dialogical, interactive and relationship development-oriented strategies with social media as a part of public relations, it is also thought to contribute to the development of theory and practice. As previous studies have focused on how web-based communication is used for public relations purposes, this study aims to reveal what is published about public relations on X (Twitter) and how the features of the platform can contribute to public relations practices. In order to examine how public relations discourse is represented on social media, the contents obtained by using the hashtags #halklailiskiler and # publicrelations on X (Twitter) were analyzed. Using content analysis, an exploratory research focused on the type of messages shared and the themes that emerged about public relations were evaluated qualitatively. As a result of the research, the possibilities of acquiring, developing and distributing information in the field of public relations and the ability to strengthen the public relations strategy of social media are emphasized. Since the study covers a two-month period and is researched through a single medium, it has been interpreted with limited data.